1978
DOI: 10.1002/ana.410040408
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent seizures induced by cortical iron injection: A model of posttraumatic epilepsy

Abstract: A single injection of 5 or 10 microliters of ferrous or ferric chloride into rat or cat sensorimotor cortex resulted in chronic recurrent focal paroxysmal electroencephalographic discharges as well as behavioral convulsions and electrical seizures. Iron-filled macrophages, ferruginated neurons, and astroglical cells surrounded the focus of seizure discharge. Recurrent focal epileptiform discharges caused by cortical injection of iron salts suggests that the development of human posttraumatic epilepsy may depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1
6

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(103 citation statements)
references
References 33 publications
2
94
1
6
Order By: Relevance
“…and positioned in a stereotaxic frame. After a small craniotomy and opening of the dura, 1.0 l of 100 mM ferrous chloride solution, or saline for control, was injected into sensorimotor cortex (1.5-2.0 mm posterior to bregma, 1.0 -1.5 mm lateral to midline, and 0.5-1.0 mm below the cortical surface) at a rate of 0.2 l/min using a microprocessor-controlled syringe pump (Model 210; Stoelting, Wood Dale, IL) (Willmore et al, 1978).…”
Section: Animal Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…and positioned in a stereotaxic frame. After a small craniotomy and opening of the dura, 1.0 l of 100 mM ferrous chloride solution, or saline for control, was injected into sensorimotor cortex (1.5-2.0 mm posterior to bregma, 1.0 -1.5 mm lateral to midline, and 0.5-1.0 mm below the cortical surface) at a rate of 0.2 l/min using a microprocessor-controlled syringe pump (Model 210; Stoelting, Wood Dale, IL) (Willmore et al, 1978).…”
Section: Animal Preparationmentioning
confidence: 99%
“…Extravasation of red blood cells results in accumulation of heme and ferric/ ferrous compounds and production of reactive oxygen species within the brain parenchyma and increases the risk for development of posttraumatic epilepsy (Willmore et al, 1978(Willmore et al, , 1983Graham and Lantos, 1997;Annegers et al, 1998;Frey, 2003;Messori et al, 2005). Intracortical injection of ferrous chloride recapitulates several key features of posttraumatic epilepsy, including physical injury and accumulation of ferric/ferrous compounds in the brain parenchyma (Willmore et al, 1978), and is associated with a high incidence of generalized recurrent seizures in rats, guinea pigs, cats, and Macaca mulatta monkeys (Willmore et al, 1978;Hammond et al, 1980;Lange et al, 1980;Reid and Sypert, 1980).…”
Section: Reactive Astrocytes In An Experimental Model Of Posttraumatimentioning
confidence: 99%
“…In our hands, laboratory analysis of this adjacent, gliotic, hemosiderin-laden tissue has shown a 20-fold increase in iron content when compared with controls (32). It is possible that the iron contained within adjacent hemosiderin-stained brain is biologically active and represents the human correlate of the iron model of epilepsy, which has been described in experimental animals (33)(34)(35)(36). An attempt to excise completely all hemosiderinladen brain may explain the prolonged, excellent surgical outcome in our series when compared with previous reports.…”
Section: Discussionmentioning
confidence: 80%
“…Sub-pial or cortical infection of ferrous or ferric chloride into cat, rat and monkey can produce epileptiform discharges (5,6). Intracerebral Injection of ferrous sulfate into rabbits or cortical iron injection into rats can produce recurrent seizures, used as model of post-traumatic epilepsy (7,8). These materials showed that iron may be causally related to the development of trauma-induced epileptiform focus in humans.…”
Section: Discussionmentioning
confidence: 99%